2023
DOI: 10.1029/2023gl105938
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Chorus Subpackets in the Earth's Magnetosphere

Huayue Chen,
Xueyi Wang,
Lunjin Chen
et al.

Abstract: Chorus subpackets/subelements are the wave packets occurring at intervals of ∼10–100 msec and are suggested to play a crucial role in the formation of substructures within pulsating aurora. In this study, we investigate the evolution of subpackets from the upstream to downstream regions. Using Van Allen Probe A measurements, we have found that the frequency of the upstream subpackets increases smoothly, but that of the downstream subpackets remains almost unchanged. Through a simulation in the real‐size magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…However, we have found that S could change during subpacket formation. The values of S estimated from electron hole in our simulation is well verified by the S th given by Equation , indicating that the irregular frequency chirping between adjacent subpackets (Crabtree, Gurudas Ganguli, & Tejero, 2017; H. Chen, Wang, et al., 2023; Santolík et al., 2014; Tsurutani et al., 2020; Zhang et al., 2020) is due to nonlinear physics. By assuming S ∼ −0.4, Vomvoridis et al.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…However, we have found that S could change during subpacket formation. The values of S estimated from electron hole in our simulation is well verified by the S th given by Equation , indicating that the irregular frequency chirping between adjacent subpackets (Crabtree, Gurudas Ganguli, & Tejero, 2017; H. Chen, Wang, et al., 2023; Santolík et al., 2014; Tsurutani et al., 2020; Zhang et al., 2020) is due to nonlinear physics. By assuming S ∼ −0.4, Vomvoridis et al.…”
Section: Discussionsupporting
confidence: 79%
“…They play a crucial role in electron dynamics, including the acceleration of hundreds of keV electrons (Meredith et al., 2001; Omura et al., 2019; Thorne et al., 2013), and the precipitation of tens of keV electrons (L. Chen et al., 2020; Ozaki et al., 2018) due to pitch angle scattering/diffusion (Liu et al., 2015; Xiao et al., 2009, 2010). The spectrum of chorus waves typically contains discrete rising tone elements, and each element consists of a series of subpackets, with wave amplitude modulation at intervals of ∼10–100 milliseconds (R. Chen, Tsurutani, et al., 2022; H. Chen, Wang, et al., 2023; Crabtree, Gurudas Ganguli, & Tejero, 2017; Santolík et al., 2003, 2014; Tsurutani et al., 2020; Zhang et al., 2020). The subpackets have been suggested to play an important role in producing the fine structures in microbursts (Miyoshi et al., 2015; Ozaki et al., 2018) and electron acceleration (Foster et al., 2021; Kubota & Omura, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear wave‐particle interactions have been suggested to play an important role in amplitude modulation of chorus subpackets (H. Chen, Wang, Chen, Omura, Lu, et al., 2023; Chen, Wang, Chen, Omura, Tsurutani, et al., 2023; Crabtree, Ganguli, & Tejero, 2017; Hanzelka et al., 2020; Tao et al., 2017; Zonca et al., 2022). A majority consensus is that the energy transfer between subpackets and particles is conserved (O’Neil, 1965; Tao et al., 2017), similar to the process of Landau resonance in classical models.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…It is believed that the intense chorus subpackets are generated due to nonlinear electron trapping through cyclotron resonance (H. Chen, Wang, Chen, Omura, Lu, et al, 2023;Chen, Wang, Chen, Omura, Tsurutani, et al, 2023;Demekhov et al, 2020;Hanzelka et al, 2020;Omura, 2021;Tao et al, 2017;Wang et al, 2024). Previous literature speculated that the energy transfer process during subpacket formation is similar to that in Landau resonance, where the energy transfer between subpackets and resonant electrons is conserved (Tao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Chorus waves are intense and coherent electromagnetic emissions in the Earth's magnetosphere (Burtis & Helliwell, 1969; Chen, Wang, et al., 2023; Li et al., 2009; Tsurutani et al., 2009; Tsurutani & Smith, 1974), excited by the injections of ∼10–100 keV electrons associated with substorms (Meredith et al., 2003; Li et al., 2009; Ma et al., 2022. These waves are scientifically interesting due to their crucial roles in modulating electron dynamics.…”
Section: Introductionmentioning
confidence: 99%